The relationship between self-directed learning and academic success in nursing students of Ahvaz Jondishapur University of Medical Sciences - Faezeh Larki; shahram Molavynejad; Alireza Momeni; Mojdeh Fathi (فصلنامه ابن سینا)
Background: Learning is the key to entering of a knowledge-based society and is the main topic of any kind of education. This study was aimed to investigate the relationship between self-directed learning and academic achievement among undergraduate nursing students in Ahvaz University of Medical Sciences. Materials and methods: This cross-sectional analytical study was performed on 230 nursing students. Students were randomly selected. The data collection tool was Fisher's Self-Learning Questionnaire. Results: The results showed that there was no relationship between self-directed learning and academic achievement of nursing students. However, there was a positive and significant relationship between self-management and academic success (p<0.05). Conclusion: Self-directed learning cannot predict the academic achievement of nursing students.